First principles investigations of electronic, photoluminescence and charge transfer properties of the Naphtho[2,1-b:6,5-b′]difuran and its derivatives for OFET - Aijaz Rasool Chaudhry; Ahmed, R.; Ahmad Irfan; Shaari, A.; Hasmerya Maarof; Abdullah G. Al-Sehemi (Universiti Kebangsaan Malaysia, 2014)
We have designed new derivatives of naphtha [2,1-b:6,5-b′] difuran as DPNDF-CN1 and DPNDF-CN2. The molecular structures of DPNDF, its derivatives DPNDF-CN1 and DPNDF-CN2 have been optimized at the ground (S0) and first excited (S1) states using density functional theory (DFT) and time-dependent density functional theory (TD-DFT), respectively. Then the highest occupied molecular orbitals (HOMOs), the lowest unoccupied molecular orbitals (LUMOs), photoluminescence properties, electron affinities (EAs), reorganization energies (λs) and ionization potentials (IPs) have been investigated. The balanced λ(h) and λ(e) showed that DPNDF, DPNDF-CN1 and DPNDF-CN2 would be better charge transport materials for both hole and electron. The effect of attached acceptors on the geometrical parameters, electronic, optical and charge transfer properties have also been investigated.